The Potential of Natural Ingredients as Anti Pediculosis capitis: A Narrative Review - Intan Nur Laili Izzah; Selviani Eka Suci; Yuliani Dewi; Nia Yuniarsih (HM Publisher, 2022)
Head louse (Pediculus humanus capitis) is a small parasite that feeds itself by sucking human blood, which causes infection of the scalp so that it becomes inflamed. The most common way to kill fleas is through the use of pharmaceutical insecticides. Some insecticide products contain permethrin, lindane, and DDT which are toxic to the body and are not easily biodegradable in the environment. Uncontrolled use of insecticides can make ticks resistant to these insecticides. Lemon, kirinyuh leaves, pandan wangi, Srikaya leaves, garlic, jarak pagar, citronella leaves, papaya, and lime have potential as anti-parasitic head lice.